Transfusion Risk Factors in Low-Energy Pelvic Fractures: A Retrospective Cohort Study - Hieronim Kołodziejczyk MD; Filip Brzeszczyński MB, BCh, BAO; Oktawiusz Bończak MD, PhD (Geriatric Orthopaedic Surgery & Rehabilitation)
Introduction The management of low-energy pelvic fractures poses a multifaceted challenge in orthopedic and geriatric care. With an increasing prevalence of patients taking new oral anticoagulant medications, it is unclear, which patients with pelvis fractures will have a significant life threatening bleed. The aim of this study was to assess the main risk factors leading to blood transfusion and longer hospital stay in patients with low-energy pelvic fractures. Materials and Methods This single center retrospective observational study was performed with reference to STROBE guidelines. Demographic data, bleeding risk factors as well as blood transfusion rates were recorded. Initially, a univariate regression analysis was performed to analyze factors associated with blood transfusion. Significant variables were selected and a multidimensional predictive model was built based on variables that showed a significant relationship with the transfusion occurrence. Results In total 167 patients were included in the study, there were 24 male and 143 female patients. The number of patients requiring blood transfusion was 20 (12%). Following univariate analysis, in final multivariate regression model, the only variable factors predicting the need for blood transfusion were low hemoglobin level on first hospital assessment (9.85 g/dl in transfused group vs 12 g/dl in non-transfused group, OR: 0.364, P < 0.005). First control hemoglobin check after 24 hours was also a significant predictor of transfusion (8.45 g/dl in transfused group vs 11.20 in non-transfused group, OR: 0.347, P < 0.005). The area under curve analysis for ROC showed good predictive accuracy for blood transfusion in patients with low haemoglobin level on first assessment (AUC = 0.9) and for first control haemoglobin (AUC = 0.88). Conclusions We suggest that all patients following low energy pelvic fractures have a haemoglobin level assessment in the emergency department. Patients with initial haemoglobin <10 g/dl should be considered for hospital admission and repeat blood tests within the first 24 hours.